Digitalization of Sharia Banking: The Influence of Self Service Technology on The Satisfaction of Millenial Customers - Juliana Nasution; Saparuddin Siregar; Sugianto Sugianto (Journal of Finance and Islamic Banking, 2022)
Digitalization has penetrated the world of Islamic banking for a long time, including in the form of Self Service Technology, including mobile banking. The purpose of this study was to see whether the dimensions of the quality of mobile banking affect customer satisfaction. The author conducted a survey using a questionnaire distributed to the millennial generation in the city of Medan. The collected data was then analyzed using SPSS 25 using the multiple linear regression analysis methods. The results of data analysis show that simultaneously, the quality of SST has an effect on customer satisfaction. The dimensions of security/privacy in mobile banking partially affect the satisfaction of millennial Islamic banking customers. While other dimensions, namely enjoyment, design/aesthetics, sociality, and practicality, partially have no effect. The results of this study indicate that customer satisfaction can be explained by all variables in the study of 69.8%. Based on these results, Islamic banking needs to improve the performance of mobile banking. Banking digitalization must pay attention to the quality dimension, not just converting banking services into digital form.